1988
DOI: 10.2307/1130404
|View full text |Cite
|
Sign up to set email alerts
|

Infant Imitation and Memory: Nine-Month-Olds in Immediate and Deferred Tests

Abstract: The ability of 9-month-old infants to imitate simple actions with novel objects was investigated. Both immediate and deferred imitation were tested, the latter by interposing a 24-hour delay between the stimulus-presentation and response periods. The results provide evidence for both immediate and deferred imitation; moreover, imitative responding was not significantly dampened by the 24-hour delay. The findings demonstrate that there exists some underlying capacity for deferring imitation of certain acts well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
144
1
7

Year Published

1988
1988
2004
2004

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 426 publications
(162 citation statements)
references
References 11 publications
8
144
1
7
Order By: Relevance
“…There is no delay imposed between showing the object on Day 2 and infants' being able to act on it. Under these circumstances, infants in the same age range tested by Diamond (1985) and in the current study exhibit representation and memory after delays compatible with those reported here, that is, 24 hr or longer (Klein & Meltzoff, 1999;Meltzoff, 1988aMeltzoff, , 1988b.…”
Section: Memorysupporting
confidence: 85%
See 1 more Smart Citation
“…There is no delay imposed between showing the object on Day 2 and infants' being able to act on it. Under these circumstances, infants in the same age range tested by Diamond (1985) and in the current study exhibit representation and memory after delays compatible with those reported here, that is, 24 hr or longer (Klein & Meltzoff, 1999;Meltzoff, 1988aMeltzoff, , 1988b.…”
Section: Memorysupporting
confidence: 85%
“…For example, studies that investigated retention using deferred imitation (Hayne, Boniface, & Barr, 2000;Klein & Meltzoff, 1999;Meltzoff, 1988b) have documented recall memory after delays of 24 hr and longer at 6, 9, and 12 months of age. One difference between the deferred-imitation and the object-occlusion procedures is that the former involves recalling an action to perform on an object, whereas the latter involves recalling an object's hidden location.…”
mentioning
confidence: 99%
“…He also imitated other novel actions, including pressing a button, pulling apart a dumbbell, and pushing down a collapsible cup. It is noteworthy that the tests were administered in a highly structured way that has been found to facilitate performance in nonverbal infants and children with Down syndrome (Meltzoff, 1988;Rast & Meltzoff, 1995).…”
Section: Motor Imitation and Object Permanencementioning
confidence: 99%
“…Meltzoff (1985) found deferred imitation of a simple action after a 1-day delay in 14-month-olds. Recently, it has been reported that infants as young as 9 months of age can observe an adult's behavior on one day and then delay their production of it for 24 hr (Meltzoff, 1988a).…”
mentioning
confidence: 99%
“…A second type of design, sometimes reported in the literature, is one in which infants are permitted to imitate the adult immediately and then to repeat the imitation after a delay without any further modeling. McCall et al (1977) used both types of procedures, and the studies by Meltzoff (1985Meltzoff ( , 1988a used only the type in which no immediate imitation was permitted. These authors and others (Flavell, 1985;Piaget, 1962) all concur that the more stringent test of memory and deferred imitation is posed by the first type of design (the one adopted here), in which the infants are not merely repeating their own behavior but committing to memory an act that is as yet unperformed by them.…”
mentioning
confidence: 99%